2023
DOI: 10.1590/fst.101622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drying and cooking treatments on phytochemicals and antioxidant activity in broccoli: an experimental in vitro study

Abstract: The current study aimed to assess broccoli's phytochemical profile and determine its antioxidant activity. Fresh broccoli was procured from a local farm and divided into two major treatment groups (cooked and dried). There were five sub-treatments in the cooking group (conventional, microwave, boiling, blanching, and steaming) and three treatments in the drying group (sun drying, freeze drying, and hot air drying). Ascorbic acid content, total carotenoids, TPC, TFC, and antioxidant activity were evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Different results were obtained in a study by Özgür et al in 2011 [ 27 ], where the total content of polyphenolic compounds in green bell peppers was reduced from 96.04 to 55.47 mg GAE/g during conventional oven drying, and in a study by Hameed et al in 2023 [ 28 ], where steamed fresh green broccoli ( Brassica oleracea ) showed a higher total content of polyphenolic compounds (191.75 mg/g d.b.) compared to samples after microwave treatments (180.03 mg/g d.b.)…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Different results were obtained in a study by Özgür et al in 2011 [ 27 ], where the total content of polyphenolic compounds in green bell peppers was reduced from 96.04 to 55.47 mg GAE/g during conventional oven drying, and in a study by Hameed et al in 2023 [ 28 ], where steamed fresh green broccoli ( Brassica oleracea ) showed a higher total content of polyphenolic compounds (191.75 mg/g d.b.) compared to samples after microwave treatments (180.03 mg/g d.b.)…”
Section: Resultsmentioning
confidence: 92%
“…), relative to the raw material [ 26 ]. Also, in a study conducted by Hameed et al in 2023 [ 28 ], it was shown that a steam treatment of fresh green broccoli (Brassica oleracea) preserves higher antioxidant activity (58.80 DPPH (%)) (expressed as a percentage of DPPH radical neutralization) than a microwave treatment (54.95 DPPH (%)). However, in the same experiment, a hot-air treatment (oven roasting) (expressed as a percentage of neutralized DPPH radicals) proved almost as beneficial as the steam treatment and gave the tested broccoli an antioxidant activity of 58.36 DPPH (%) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants have been proven to have an essential role in preventing cancer, cardiovascular diseases, diabetes, neurological diseases and immune system diseases by clearing reactive species in the body [14]. Phenolic compounds are natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%